Simulating Potential Associated Socio-Economic Determinants With Sustainable Food Security (A Macro-Micro Spatial Quantitative Model) - Mohammad Reza Pakravan-Charvadeh; Cornelia Flora; Haider A. Khan (Frontiers Media S.A., 2022)
Improving sustainable food security status, nowadays, is an important challenge globally, especially in developing countries. The policy goal should be equity-everyone has the same opportunity to be food secure-rather than equality-everyone gets the same subsidy. Since the culture and socioeconomic status within a country vary from region to region, collapsing all areas into a unique region may introduce errors and inaccurate results, as most studies carried out. This study assesses the geographical pattern of association between food security and socioeconomic factors in urban areas in Iran using a nationally and regionally representative household consumption-expenditure survey from 2010 to 2018. The logistic regression model and big data are used to achieve this goal. The results show that a substantial number of households face food insecurity in urban areas in Iran. Also, different geographic regions have various salient factors that affect food insecurity. Aggregation tests confirmed that researchers should estimate separate models for different provinces, states, and districts to assess and monitor the food security status of a country instead of estimating a unique model for the whole of the country. Geographical disparities should be considered as an important issue before suggesting any catch-all policies for a country. The geo-locational factor of households is a key determinant of the association between socioeconomic factors and food security in urban areas in Iran. In sum, the practical suggestions for improving Iranian households' food security in urban areas are as follows: (1) Developing job opportunities for the head of household. (2) Enhancing the potential for self-employment. (3) Facilitating the study of children within households including providing inexpensive uniforms, books, and materials, especially for poor households. (4) Supporting young couples in terms of accessing to financial resources and providing inexpensive essential equipment of home for them; and (5) Introduction of the importance of dietary diversity and different foods which can be cooked by using these food ingredients within a household. Comparative case studies using similar methodologies can test if our results are generalizable.